Implementasi Kaidah Muamalah pada Percetakan CV. Nekad Romo untuk Meningkatkan Kualitas Karyawan - Prayogo, Singgih; Angkasa, Nawa (Institut Agama Islam Negeri Metro, 2023)
This study is to provide exposure or results of the implementation of Islamic business ethics in an effort to improve employee performance in one's business. This study uses descriptive qualitative methods to determine the perspective of Islamic values in the implementation of Islamic business ethics in employee performance. The object or place taken in this research is World Romo Romo which is engaged in the Romo and advertising business at Jalan Terong Metro Timur Address, Metro City. Data taken using primary data obtained from interviews with business owners, employee representatives and customer representatives by testing the validity of the data using triangulation. Data collection techniques through interviews, observation, and also documentation.